Impact of Financial Deepening on Economic Growth in Indian Perspective: ARDL Bound Testing Approach to Cointegration - Ghildiyal, Vipin; Pokhriyal, A.K; Pokhriyal, A.K; Mohan, Arvind (Asian Development Policy Review, 2015)
The present work is an attempt to investigate into the causal impact of financial deepening on economic growth in case of India. For analyzing the long term equilibrium relationship between the desired variables, we have employed Autoregressive Distributed Lag (ARDL) Bound testing approach. ARDL being a new approach is an improvement over the other traditional techniques of cointegration. Further, using the Granger Error Correction Model (ECM) technique we have tried to estimate the causal impact in the short run also. The findings suggest that there exist an equilibrium relationship in long run between financial deepening and economic development. Results suggested that financial deepening causes economic growth in the long run and also in the short run. Therefore, it is concluded that for enhancing the economic growth the government has to take effort to improve the financial deepening. Special efforts should be put to provide easy credit to private sector, stock market development and also to foster foreign trade.